Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 9 - Quadratic Functions and Equations - 9-5 Completing the Square - Practice and Problem-Solving Exercises - Page 564: 18



Work Step by Step

$z^2-2z=323$ Compare it with the standard form of quadratic equation $ax^2+bx+c$, we have $a=1, b=-2$ Therefore, $b^2=4ac$ $\implies$ $c=\dfrac{b^2}{4a}$ Thus, $c=\dfrac{b^2}{4a}=\dfrac{(-2)^2}{4}=1$ To complete the square, add $1$ on both sides. $z^2-2z+1=323+1$ $\implies (z-1)^2=324$ $\implies (z-1)=18$ and $\implies (z-1)=-18$ or, $z=19,-17$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.